2008
DOI: 10.1016/j.aorn.2008.02.020
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Incidence of Anesthetic Adverse Events in Late Afternoon Surgeries

Abstract: ANESTHETIC ADVERSE EVENTS have been found to occur more frequently in surgical procedures performed after 4 PM. THE MAJOR FACTORS that contribute to increased anesthetic adverse events include fatigue, circadian rhythm lows or dips, and administrative delays. AN INCREASED SHORTAGE of anesthesia care providers is likely to create longer work hours, thus increasing fatigue, which can lead to more anesthetic adverse events. Awareness of and education about adverse events and solutions are imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The case-mix of patients is an important determinant of outcome and variation during times of the day and days of the week and likely explains, at least in part, the after hours increased mortality effect seen in many studies conducted in other conditions to date (14). Reduced staffing or decreased access to tests and procedures in the after hours and health care worker fatigue and resulting error in the after hours may be contributors (5,15,16). Institutional status as a teaching facility may also play a role (4).…”
Section: Discussionmentioning
confidence: 99%
“…The case-mix of patients is an important determinant of outcome and variation during times of the day and days of the week and likely explains, at least in part, the after hours increased mortality effect seen in many studies conducted in other conditions to date (14). Reduced staffing or decreased access to tests and procedures in the after hours and health care worker fatigue and resulting error in the after hours may be contributors (5,15,16). Institutional status as a teaching facility may also play a role (4).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies conducted in hospitalized populations have identified reduced staffing or decreased access to tests and procedures as potential means to explain excess mortality risk associated with off hours admissions [ 3 , 11 , 27 ]. It has been shown that adverse anaesthetics events are more common after 16:00 with inciting causes felt to be fatigue and disrupted circadian rhythms [ 28 ]. Although our trauma surgeons universally reported concerns with fatigue with the call schedule used during this study period (it has been reduced since June 2008), no association with after-hours or weekend admission and adverse outcome was shown.…”
Section: Discussionmentioning
confidence: 99%
“…At most medical institutions, staffing levels dramatically decrease during off hours; i.e., nights and weekends. At such times, experienced doctors in supervisory roles and consultants in subspecialties are less available [ 1 ], and staff performance can be impaired because of fatigue and disrupted circadian rhythms [ 2 ]; consequently, more medical errors [ 3 , 4 ] and complications [ 5 ] tend to occur. Off-hour presentation is therefore known to be a risk factor for patients presenting with unplanned critical conditions requiring rapid diagnosis and aggressive intervention, including cardiac arrest [ 6 ], myocardial infarction [ 7 ], stroke [ 1 ], ruptured aortic aneurysm [ 8 ], acute epiglottis [ 8 ], and pulmonary embolism [ 8 ].…”
Section: Introductionmentioning
confidence: 99%